Computational insight into excited states of the ring‐opening radicals from the pyrolysis of furan biofuels. Issue 9 (9th October 2018) - Li, Yuanyuan; Gan, Yanzhen; Cao, Zexing
Abstract : The low‐lying valence excited states and Rydberg states of the radical species from the ring‐opening reactions in pyrolysis of furan biofuels have been determined by extensive density functional theory and sophisticated wave function theory calculations. The radicals 1‐C4 H5 O‐2, 2‐furylCH2, and 4‐C6 H7 O with the delocalized π‐type single electron are predicted to be most stable among the reactive species here for furan, 2‐methyfuran, and 2, 5‐dimethylfuran, respectively. Predicted vertical transition energies by TD‐CAM‐B3LYP show good agreement with those by CASPT2. Some among the electronic excitations to low‐lying states can take place in the visible light region, and they may be involved in the combustion process. Further surface hopping dynamics simulations on the excited states of the most stable ring‐opening radical 1‐C4 H5 O‐2 of furan as an example reveal that 89.9% sampling trajectories at the initial excited state of 2 2 A"(π 1 π* 2 ) decay to the 1 2 A'(n 1 π* 2 ) state within an average of 384 fs, and then 81.2% trajectories at the 1 2 A' state go to the ground state within an average of 114 fs. At the end of the simulation for 1000 fs, 18.8% trajectories still stay on the excited states of 2 2 A" and 1 2 A', suggesting that the reactive radicals in the ground state are mainly responsible for the combustion chemistry of furan biofuels. © 2018 Wiley Periodicals, Inc. Abstract : The low‐lying valence excited states and Rydberg states of the ring‐opening radicals from the pyrolysis of furan biofuels have been studied by extensive theoretical calculations, and the present results enrich the knowledge of such pyrolytic reactive species in their ground and excited states and provide a basis to understand the role of the excited intermediates in combustion.